The psychoactive cathinone derivative pyrovalerone alters locomotor activity and decreases dopamine receptor expression in zebrafish (Danio rerio). Issue 11 (18th October 2019) - Souders, Christopher Laurence; Davis, Robert H.; Qing, Hua; Liang, Xuefang; Febo, Marcelo; Martyniuk, Christopher J.
Abstract: Introduction: Pyrovalerone (4‐methyl‐β‐keto‐prolintane) is a synthetic cathinone (beta‐keto‐amphetamine) derivative. Cathinones are a concern as drugs of abuse, as related street drugs such as methylenedioxypyrovalerone have garnered significant attention. The primary mechanism of action of cathinones is to inhibit reuptake transporters (dopamine and norepinephrine) in reward centers of the central nervous system. Methods: We measured bioenergetic, behavioral, and molecular responses to pyrovalerone (nM‐µM) in zebrafish to evaluate its potential for neurotoxicity and neurological impairment. Results: Pyrovalerone did not induce any mortality in zebrafish larvae over a 3‐ and 24‐hr period; however, seizures were prevalent at the highest dose tested (100 µM). Oxidative phosphorylation was not affected in the embryos, and there was no change in superoxide dismutase 1 expression. Following a 3‐hr treatment to pyrovalerone (1–100 µM), larval zebrafish (6d) showed a dose‐dependent decrease (70%–90%) in total distance moved in a visual motor response (VMR) test. We interrogated potential mechanisms related to the hypoactivity, focusing on the expression of dopamine‐related transcripts as cathinones can modulate the dopamine system. Pyrovalerone decreased the expression levels of dopamine receptor D1 (~60%) in larval zebrafish but did not affect the expression of tyrosine hydroxylase, dopamine active transporter, or any other dopamine receptor subunit examined, suggesting that pyrovalerone may regulate the expression of dopamine receptors in a specific manner. Discussion: Further studies using zebrafish are expected to reveal new insight into molecular mechanisms and behavioral responses to cathinone derivates, and zebrafish may be a useful model for understanding the relationship between the dopamine system and bath salts. Abstract : Hypoactivity is induced by pyrovalerone in zebrafish larvae.